Organic Zinc and Selenium Supplementation of Late Lactation Dairy Cows: Effects on Milk and Serum Minerals Bioavailability, Animal Health and Milk Quality - Gabriel S. Klein; Karoline W. Leal; Camila A. Rodrigues; Taynara M. R. Draszevski; Andrei L. R. Brunetto; Maksuel G. Vitt; Mathias S. Klein; Vitoria H. Cauduro; Erico M. M. Flores; Gilnei B. da Silva; Margarete D. Bagatini; Alana B. de M. Chitolina; et al. (Animals)
This study determined whether organic zinc and selenium supplementation of late lactation dairy cows positively affects immunity, oxidative status, milk quality (especially mineral levels), biochemical and hematologic parameters, and production efficiency. Twenty Jersey cows were divided into three groups: Control (n = 6)—without organic supplementation; Zinc (n = 7)—zinc supplementation (zinc amino acid chelate) and Selenium (n = 7)—selenium supplementation (selenium amino acid complex). The basal diet contained inorganic minerals. Blood and milk samples were collected on days 1, 14 and 28. Serum selenium concentration was higher in the Selenium group, and zinc level in milk was higher in the Zinc group. On day 28, supplementations resulted in higher lymphocyte counts, and lower serum creatine kinase, myeloperoxidase activity, levels of reactive oxygen species, thiobarbituric acid-reactive substances, and iron. In milk, lower somatic cell count was also observed when cows were zinc or selenium supplemented compared to the control. Lower serum cholinesterase activity and higher heavy chain immunoglobulin concentration were observed on days 14 and 28. Selenium supplementation resulted in a higher immunoglobulin A concentration on days 14 and 28, and lower ceruloplasmin concentration on day 28 compared to Control, as well as a lower haptoglobin concentration on day 28. The Selenium group also had lower milk fat content compared to the Control. Supplementations changed the milk fatty acid profile, producing a higher unsaturated fatty acid/saturated fatty acid ratio. There was no effect on lactation persistence. It is concluded that mineral supplementation with selenium and zinc benefits immune, antioxidant, and anti-inflammatory responses. Conversely, milk quality was affected both positively and negatively.